Enhancement of Power Quality in Four Bus System Using Hybrid Power Flow Controller. Issue 1 (1st December 2022) - Suganya, R.; Anitha, M.; Pugazhendiran, P.
Abstract: To mitigate the impacts of voltage sag, a hybrid power flow controller (HPFC) finds a spot between the sending and receiving terminals. This research work deals with the comparison of four bus systems employing UPFC and HPFC. Simulation is done for 4 bus system using UPFC and HPFC. The outcomes are associated with respect to the voltage, active power and Reactive power. The outcomes exemplifies the grander enactment of HPFC controlled 4 bus system compared to UPFC controlled 4 bus system.